The “Corporeality” of the Image in Walter Gropius’ Monumentale Kunst und Industriebau Lecture - Mejía Moreno, Catalina (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
The introduction of a series of traded photographs of North and South American Silos into the discourse of modern architecture has been generally attributed to the German architect Walter Gropius when he published the photographs in the 1913 Jahrbuch des Deutschen Werkbundes. What remains overlooked is the photographs’ original dissemination platform: Gropius’ Monumentale Kunst und Industriebau Lichtbildervortrag [lantern slide lecture] from 1911. Based on a close reading of archival material – first the original lecture manuscript, which indicates that images and text were merged in performance, and then the photographic slides – this paper argues that the projector’s agency enables the foundation of these iconic buildings’ architectural criticism. Indeed such criticism actually takes place in the ephemeral space of the projection, rather than in the various printed media where it is usually located.